(3CNHGQ ecI TQagG Gddg heG LGA ajgG ef GdBKGQs - (3GdCRQbj , eMeO Hf YHO Gddg Hf CMeO Hf eMeO Hf GdhdjO Hf YbHg Hf GdCRQb, CHh GdhdjO,J (B250 (3g` s ((3eMeO Hf YHO GdbGOQ Hf Ydi Hf fGUQ Gdeci GdTGaYi s)
(3ChdgG (B:s
(3GNHQfi hGdOi Gdabjg GdGeGeGHh MaU YeQ Hf YHO GdeLjO Hf YeQ GdbQTi GdejGfTi s
(3BNQgG (B:s
(3hGdQGMI Ohf GdMOjHjI Ydi jSGQ GdPGgH Edi LOI GdHZjHZI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B198s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdGJQGc (B- (3GdGRgQ (B((3JGQjN (B945) s
Keywords: (3GdJGQjNs